THU0248 Therapeutic Interest of anti-CD3 and Anti-Baff Monoclonal Antibodies in The Nod Model of Sjögren's Syndrome. (15th July 2016) - Felten, R.; Chatenoud, L.; Magne, L.; Sawaf, M.; Seifert, C.; Dumortier, H.; Monneaux, F.; Sibilia, J.; Schneider, P.; Gottenberg, J.-E.
Abstract : Background: BAFF is an essential cytokine for autoreactive B-cell activation, survival, and autoantibody secretion. Therapeutic interest of anti-BAFF therapy is under evaluation in primary Sjögren's syndrome (pSS) with encouraging data in an open clinical trial but it has not been evaluated in an animal model of the disease. In addition, T-lymphocytes, which represent the predominant cell population infiltrating salivary glands, also contribute to its pathogenesis. Targeting T-cells with anti-CD3 antibodies is efficacious to control diabetes in NOD mice, which also represent a relevant animal model of pSS, and in patients with type I diabetes. Objectives: We aimed to evaluate the therapeutic effect of anti-CD3 and anti-BAFF antibodies and their potential synergy on dryness and salivary gland infiltrates in the NOD model of pSS. Methods: Female NOD mice were studied between 10 and 20 weeks. 8 mice were treated with anti-BAFF antibodies, 8 with isotype control antibodies, 6 with the combination of anti-BAFF and anti-CD3 antibodies, 5 with anti-CD3 antibodies and 12 were not treated. Dryness was assessed by measuring the stimulated salivary flow at 10 and 20 weeks. Focus score was analysed at 20 weeks. Spleen, salivary glands and blood lymphocyte sub-populations were analysed using flow cytometry. Results: Only anti-BAFF antibody therapy led to a significant increase in the salivary flow (10.4μL/20 minutes/g ±1.3 with anti-BAFF antibodies, 5.7±2.7 with isotype control antibodies, p=0.003, 5.5±1.7 in non-treated mice, p=0.002) and resulted in the decrease in salivary gland infiltrates (focus score of 1.75±0.5 with anti-BAFF antibodies, 4.0±0 with isotype control antibodies, p=0.028, 4.6±1.14 in non-treated mice, p=0.015). Inhibition of BAFF resulted in a marked decrease of blood, spleen and salivary B-cells (proportion of B-lymphocytes out of total number of lymphocytes in salivary glands: 1.0%±0.9 with anti-BAFF antibodies, 7.6%±2.6 with anti-CD3 antibodies, 0.3%±0.2 with combined treatment and 12.5%±2.3 with isotype control). With anti-BAFF and/or anti-CD3, an increase in salivary glands Foxp3+ regulatory T-cells was observed (proportion of FoxP3+ T cells among total number of CD4+ T cells: 28.7%±5.9 with anti-BAFF antibodies, 27.6%±1.8 with anti-CD3 antibodies, 27.7%±1.9 with combined treatment and 20.7%±1.0 with isotype control). In addition, salivary CD3+CD4-CD8- double negative T-cells markedly increased after anti-BAFF treatment (41.0%±5.5 with anti-BAFF antibodies, 26.4%±7.8 with anti-CD3 antibodies, 37.7%±8.9 with combined treatment and 24.8%±13.5 of T-lymphocytes CD3+ with isotype control). Salivary double negative CD4-CD8- T-cells were inversely correlated with the focus score, which suggests their protective role. Conclusions: Anti-CD3 therapy was not efficacious nor synergic with anti-BAFF. Anti-BAFF therapy resulted in a marked improvement of dryness and salivary gland infiltrates in the NOD model of pSS. Interestingly, BAFF inhibition resulted in the increase of regulatory T-lymphocyte populations, which might contribute to the therapeutic effect of this strategy. This study strengthens the rationale to target BAFF in patients with pSS. Disclosure of Interest: R. Felten Grant/research support from: Research grant from French Society of Rheumatology, L. Chatenoud: None declared, L. Magne: None declared, M. Sawaf: None declared, C. Seifert: None declared, H. Dumortier: None declared, F. Monneaux: None declared, J. Sibilia: None declared, P. Schneider: None declared, J.-E. Gottenberg: None declared